1988
DOI: 10.1113/jphysiol.1988.sp017382
|View full text |Cite
|
Sign up to set email alerts
|

The role of periodontal receptors in the jaw‐opening reflex in the cat.

Abstract: 1. In anaesthetized cats, graded electrical stimulation of the inferior alveolar nerve at just above threshold for the largest afferent fibres caused inhibition of jaw‐closer motoneurones. Stimulus strength had to be increased to 1.5 times threshold with double shocks to cause reflex contraction of the digastric muscle. 2. Inhibition of jaw‐closer muscles and excitation of digastric muscle resulted from transients of force applied to the upper canine tooth. However, the threshold for the digastric response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Mechanoreceptors within the periodontal ligament are known to inhibit jaw adductors and trigger a jaw opening response as reactions to biting on unexpectedly resistant, potentially damaging foods (Anderson et al, 1970;Dessem et al, 1988). We suggest that a system that experiences higher displacements and strains will facilitate greater opportunity for feedback through the nervous system and, hence, a greater capacity for the organism to modify behavior and avoid catastrophic failure in bones and teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanoreceptors within the periodontal ligament are known to inhibit jaw adductors and trigger a jaw opening response as reactions to biting on unexpectedly resistant, potentially damaging foods (Anderson et al, 1970;Dessem et al, 1988). We suggest that a system that experiences higher displacements and strains will facilitate greater opportunity for feedback through the nervous system and, hence, a greater capacity for the organism to modify behavior and avoid catastrophic failure in bones and teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The reflexly induced facilitation may help the muscles to maintain pieces of food between the teeth so that they may then be crushed, or it may, in concert with the muscle spindle reflex control (Lamarre & Lund, 1975;Goodwin, Hoffmann & Luschei, 1978;Dessem, Iyadurai & Taylor, 1988), help to overcome unexpected resistances to closing by a load compensation reflex. Ottenhoff et al (1992) have recently investigated the responses of the jaw-closing muscles to changing loads applied to the teeth during simulated chewing movements.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition could be seen at a force as low as 025 N but was more profound at higher forces. Dessem et al (1988) also found clear evidence for an inhibition when 1 N forces were applied to the teeth. It is not surprising that a more profound inhibition was observed with a larger applied force since it is likely that as the force is increased more of the mechanoreceptors with higher stimulus thresholds are recruited.…”
Section: Discussionmentioning
confidence: 83%
“…It has generally been thought that they have a significant role in controlling activity in the masticatory muscles. Dessem et al (1988) suggested that they could be expected to provide negative feedback control of forces exerted on the teeth during mastication and related tasks. However, the mechanical thresholds of periodontal mechanoreceptors are well documented and they range between 10 and 800 mN (for review see Linden, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation